Microbiological examination of water and wastewater - Csuros, Maria (Lewis Publishers, 1999)
Microbiological tests have proven to be an indispensable part of environmental contaminant detection. It has also been tremendously difficult to find a comprehensive training manual and laboratory manual for those procedures. Microbiological Examination of Water and Wastewater now provides that much-needed resource for laboratory trainees and environmental professionals alike." "By exploring the fundamentals of microbiology, as well as microbial metabolism, growth, control, and classification, trainees will better understand the purpose and manner of microbiological examination. Those details also make Microbiological Examination of Water and Wastewater ideal as a standard guidebook for laboratories, water and wastewater treatment plants, and the communities they serve.